Attitudes toward language and language choice in regional intermarriage families: A case study in Tangerang, Banten - Indarti, Dwi; Manara, Christine (Universitas Syiah Kuala, 2025)
Despite extensive research on language attitudes and shifts in Indonesia, studies on language choice in intercultural marriages remain scarce. Therefore, this study explores the attitudes toward heritage, national and international languages, as well as factors influencing language choice in regional intermarriage families living in Tangerang, Banten. This research employed a qualitative case study and used a purposive sampling technique to select the respondents. The respondents were four mothers whose spouses come from different regional cultural backgrounds and live in the Tangerang area. Using questionnaires and semi-structured interviews, this study revealed positive attitudes toward heritage, national, and international languages among respondents, emphasizing the significance of regional languages as crucial elements in maintaining connections with their cultural roots and fostering a sense of self-awareness and appreciation of their cultural backgrounds. However, discrepancies emerge between the parents beliefs and their actual efforts to maintain and preserve the heritage language for their children. Meanwhile, well-educated female parents perceive mastering English as essential in a globalized world. They prioritize English proficiency to provide educational opportunities for their children. This dual perspective on language reflects an attitude among the respondents that is sensitive to levels of formality and covers diverse purposes of language. On one hand, the desire to learn and use English to connect with the global community indicates an awareness of the importance of a global language for communication, education, and opportunities beyond their local context. On the other hand, their attachment to national and regional languages highlights a strong sense of cultural identity.